Can stroke specific vocational rehabilitation (SSVR) be delivered and measured?: feasibility RCT and economic analysis - Radford, Kathryn A.; Grant, Mary; Sinclair, Emma; Terry, Jane; Sampson, Christopher James; Edwards, Claire; Walker, Marion F.; Lincoln, Nadina; Drummond, Avril E.R.; Phillips, Julie; Watkins, Louise; Rowley, Emma; et al. (SAGE, 2014)
Background: